An assessment of the evaporation and condensation phenomena of lithium during the operation of a Li(d, xn) fusion relevant neutron source. Issue 12 (December 2016) - Knaster, J.; Kanemura, T.; Kondo, K.
Abstract: The flowing lithium target of a Li(d, xn) fusion relevant neutron source must evacuate the deuteron beam power and generate in a stable manner a flux of neutrons with a broad peak at 14 MeV capable to cause similar phenomena as would undergo the structural materials of plasma facing components of a DEMO like reactors. Whereas the physics of the beam-target interaction are understood and the stability of the lithium screen flowing at the nominal conditions of IFMIF (25 mm thick screen with +/–1 mm surface amplitudes flowing at 15 m/s and 523 K) has been demonstrated, a conclusive assessment of the evaporation and condensation of lithium during operation was missing. First attempts to determine evaporation rates started by Hertz in 1882 and have since been subject of continuous efforts driven by its practical importance; however intense surface evaporation is essentially a non-equilibrium process with its inherent theoretical difficulties. Hertz-Knudsen-Langmuir (HKL) equation with Schrage's 'accommodation factor' η = 1.66 provide excellent agreement with experiments for weak evaporation under certain conditions, which are present during a Li(d, xn) facility operation. An assessment of the impact under the known operational conditions for IFMIF (574 K and 10 −3 Pa on the free surface), with the sticking probability of 1 inherent to a hot lithium gas contained in room temperature steel walls, is carried out. An explanation of the main physical concepts to adequately place needed assumptions is included.